2002
DOI: 10.1037/0012-1649.38.3.438
|View full text |Cite
|
Sign up to set email alerts
|

Development of gaze aversion as disengagement from visual information.

Abstract: Older children, but not younger children, were found to look away more from the face of an interlocutor when answering difficult as opposed to easy questions. Similar results were found in earlier work with adults, who often avert their gaze during cognitively difficult tasks (A.M. Glenberg, J.L. Schroeder, & D.A. Robertson, 1998). Twenty-five 8-year-olds and 26 5-year-olds answered verbal reasoning and arithmetic questions of varying difficulty. The older children increased gaze aversion from the face of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
151
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(169 citation statements)
references
References 36 publications
16
151
1
1
Order By: Relevance
“…Glenberg, Schroeder, and Robertson (1998) asked participants moderately difficult general informational questions requiring memory searching and showed that averting gaze away from environmental distraction facilitated the allocation of cognitive resources to internal processing that enhanced performance. Doherty-Sneddon and Phelps (2005) and Doherty-Sneddon, Bruce, Bonner, Longbotham, and Doyle (2002) replicated these results with children. If lying is more cognitively demanding than truth telling, we propose that a corollary of Glenberg et al's position is that less eye movement should be evident during deception.…”
Section: Lie Detection By Inducing Cognitive Load: Averting Rehearsalsupporting
confidence: 76%
See 1 more Smart Citation
“…Glenberg, Schroeder, and Robertson (1998) asked participants moderately difficult general informational questions requiring memory searching and showed that averting gaze away from environmental distraction facilitated the allocation of cognitive resources to internal processing that enhanced performance. Doherty-Sneddon and Phelps (2005) and Doherty-Sneddon, Bruce, Bonner, Longbotham, and Doyle (2002) replicated these results with children. If lying is more cognitively demanding than truth telling, we propose that a corollary of Glenberg et al's position is that less eye movement should be evident during deception.…”
Section: Lie Detection By Inducing Cognitive Load: Averting Rehearsalsupporting
confidence: 76%
“…Stimulation from the environment can be distracting and impair internal processing (Doherty-Sneddon et al, 2002;Doherty-Sneddon & Phelps, 2005;Glenberg et al, 1998). Expanding on this notion, we predicted less eye movements for liars because their high cognitive loads focused on internal processing would have them reducing environmental distraction.…”
Section: Eye Movementsmentioning
confidence: 99%
“…It has previously been demonstrated that individuals use gaze aversion when processing cognitively demanding information (Doherty-Sneddon et al, 2002;Doherty-Sneddon & Phelps, 2005;Glenberg et al, 1998). In a social interaction people show little gaze aversion when they are listening to another person speak, rather gaze aversion predominantly occurs when people are thinking about a response and when they are speaking (Doherty-Sneddon et al, 2002;Glenberg et al, 1998). The current experiment had two phases: when participants were speaking and when participants were listening.…”
Section: Introductionmentioning
confidence: 91%
“…24 The function of fixations away from the face is quite different from those involved with picking up visual information (see Figure 2b). Deliberately averting gaze may facilitate thinking, 25 but it also sends a signal to the conversant that it is not yet their time to speak. Making regular eye movements to and away from the listener ensures that they are paying attention, as well as signalling that the speaker knows this (communication which may be more difficult via video or webcam 24 ).…”
Section: Interacting With Othersmentioning
confidence: 99%